2007
DOI: 10.1055/s-1999-970284
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Response to Professional Road Cycling: The Tour de France

Abstract: The aim of the present investigation was to evaluate the heart rate response of 8 professional cyclists (26+/-3 yr; 68.9+/-5.2 kg; V02max: 74.0+/-5.8 ml x kg(-1) x min(-1)) during the 3-week Tour de France as an indicator of exercise intensity. Subjects wore a heart rate telemeter during 22 competition stages and recorded data were analysed using computer software. Two reference heart rates (corresponding to the first and second ventilatory thresholds or VT1 and VT2) were used to establish three levels of exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
2
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 0 publications
4
72
2
5
Order By: Relevance
“…Our underlying assumptions in studies using the Session RPE method as the intensity component of monitoring training has been to use the Session RPE to replace objective measures of exercise intensity within the training impulse (TRIMP) approach originally developed by Fitz-Clarke et al 5 and Morton et al 18 and widely used by others. 6,7,12,14,15,21 The TRIMP approach is a very useful way of combining exercise intensity and duration into a single number representation of the stimulus for adaptation provided by any exercise bout, which has been limited by the absence of a simple method of expressing exercise intensity. During very prolonged exercise, the drift of Session RPE (or of HR) acts as a multiplier of exercise duration and suggests a much larger TRIMP than might have been calculated using the RPE or HR early during the exercise bout as a marker of exercise intensity.…”
Section: 9mentioning
confidence: 99%
“…Our underlying assumptions in studies using the Session RPE method as the intensity component of monitoring training has been to use the Session RPE to replace objective measures of exercise intensity within the training impulse (TRIMP) approach originally developed by Fitz-Clarke et al 5 and Morton et al 18 and widely used by others. 6,7,12,14,15,21 The TRIMP approach is a very useful way of combining exercise intensity and duration into a single number representation of the stimulus for adaptation provided by any exercise bout, which has been limited by the absence of a simple method of expressing exercise intensity. During very prolonged exercise, the drift of Session RPE (or of HR) acts as a multiplier of exercise duration and suggests a much larger TRIMP than might have been calculated using the RPE or HR early during the exercise bout as a marker of exercise intensity.…”
Section: 9mentioning
confidence: 99%
“…The training loads completed during that period were determined by multiplying the session-RPE (CR10-scale) by session duration in minutes. These session-RPE values were correlated to the training load measures obtained from three different heart ratebased methods suggested by Banister et al [16], Edwards [14], and Lucia et al [25]. All individual correlations between the various heart rate-based training loads and session-RPE were statistically significant (r values from 0.50 to 0.85).…”
Section: Discussionmentioning
confidence: 94%
“…A substantial number of scientific papers have been published describing the relationship exercise intensity and the effects of various CHO supplements during road cycling [19][20][21][22][23][24][25], but there are few scientific papers focused on the effect of maltodextrin supplementation in pre-competition or laboratory testing nor how it modifies off-road cycling performance parameters. Recent studies have found that carbohydrate drinks (glucose, maltose and sucrose administrated at 0.65 g/kg before a performance test and then 0.2 g/kg every 15 min during every 1 h of testing), when compared to a placebo (maltodextrin in low doses), increased plasma glucose levels but did not enhance performance during the test (a 1 h test) after glycogen-depletion protocol initiated [26].…”
Section: Discussionmentioning
confidence: 99%